The role of photoperiod and melatonin in seasonal biorhythms of mammals: A review - Lanszki, József (Acta Agraria Kaposváriensis, 2000)
There are periodic variations in the reproduction and moulting (hair development) of a number of domestic animal species (species and breeds producing hair fibre, wool fibre or fur) living under conditions of natural lighting. Production in these species can be made less dependent on external conditions by the appropriate application of a lighting programme or melatonin treatment. Not only is it possible to increase the specific yield of the animal product in question (e.g. wool); a reduction in the length of the rearing period can also be achieved (in the case of fur-bearing species) without any accompanying deterioration in the quality treats. An area within the application of such procedures which in future may prove significant, also from the aspect of genetic breed improvement, is artificial insemination (e.g. in the fur-bearing species). The results which have been obtained in the application of melatonin treatment can be put to good use in the development of biostimulation procedures.